2022
DOI: 10.3390/polym14132696
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extract Enrichment: Mechanical and Physicochemical Properties Improvement of Rice Starch-Pectin Composite Film

Abstract: The effects of green tea extract (GTE) at varying concentrations (0.000, 0.125, 0.250, 0.500, and 1.000%, w/v) on the properties of rice-starch-pectin (RS-P) blend films were investigated. The results showed that GTE addition enhanced (p < 0.05) the antioxidation properties (i.e., total phenolic content, DPPH radical scavenging activity, and ferric reducing antioxidant power) and thickness of the RS-P composite film. The darker appearance of the RS-T-GTE blend films was obtained in correspondence to the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
1
9
0
1
Order By: Relevance
“…These weak intermolecular bonding led to a weaker film structure, thus reducing the tensile strength and flexibility of the DPE-incorporated film. Decreases in TS and EAB were noticed in cassava starch (CS) and sodium carboxymethyl cellulose (CMC) edible films with apple polyphenols [ 62 ] and in a rice starch-pectin composite film incorporating green tea extract [ 63 ]. A decreasing EAB was also observed in gelatin-based films with mango peel extract [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These weak intermolecular bonding led to a weaker film structure, thus reducing the tensile strength and flexibility of the DPE-incorporated film. Decreases in TS and EAB were noticed in cassava starch (CS) and sodium carboxymethyl cellulose (CMC) edible films with apple polyphenols [ 62 ] and in a rice starch-pectin composite film incorporating green tea extract [ 63 ]. A decreasing EAB was also observed in gelatin-based films with mango peel extract [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…So, the FS values were not significantly affected. However, when compared to the FS of a green tea extract-infused biocomposite film [ 63 ], the FS of all the DPE-enriched biocomposite films was significantly higher, which suggested that DPE-incorporated films might not be suitable for application in packaging high-moisture foods.…”
Section: Resultsmentioning
confidence: 99%
“…The large variety of the compounds possessing the inhibition ability upon polymer degradation, namely synthesis antioxidants such as hindered phenols [ 2 , 3 ], natural extracts [ 4 , 5 ], inorganic structures as oxides [ 6 ], polyhedral oligomeric silsesquioxane (POSS) [ 7 , 8 ], complexes [ 9 ] or multicomponent blends [ 10 ] radiation crosslinking [ 11 , 12 ] have been investigated. The problem regarding the improvement of the polymer stability in the presence of antioxidants appears as the background requirement for new applications involving the long-life operation under severe conditions [ 13 , 14 ], the recycling [ 15 ] or food handling [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biopolymers were seen as an alternative to producing plastic and have garnered much attention. Starch is the most common biopolymer feedstock for producing films and coatings [ 4 ] and is extensively covered in the literature as the primary material for the implementation of active food packaging [ 5 , 6 , 7 ]. According to Charles et al [ 8 ], potato peel starch can be used in the packaging of chilled and frozen foods.…”
Section: Introductionmentioning
confidence: 99%